Adopting a sustainable approach in fast fashion corporations using the Rawlsian social contract theory - Toh, Qian Hui (Nanyang Technological University, 2020)
Following the post war industrialisation, the fashion industry has evolved rapidly, leading to the rise of the fast fashion industry. Hand-made garments has been replaced by mass production— which is often associated with a shorter production timeline and low production costs. While consumers have gotten used to the array of clothes readily available for prices as low a dollar, these prices often fail to reflect the true costs of the products— of which includes environmental and social costs. Such costs include environmental degradation as well as worsening health conditions of employees and locals as a result of unsustainable production practices. This begs the question— are fast fashion corporations obligated to ensure sustainable business practices? The goal of this paper is twofold. First, I highlight the need for fast fashion corporations to adopt sustainable practices because the current business model is one that benefits the corporations at the expense of others in the society— particularly the least advantaged people. Second, I argue that fast fashion corporations ought to adopt the Rawlsian social contract theory as an ethical framework for issues regarding sustainability. This paper will also touch on sustainable business practices which fast fashion corporations can adopt.